Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T20:04:21+01:00
-3xy<do potęgi 3>-(2xy<do potęgi 3>) = -5xy<do potęgi 3> = -5 * 1 * 2<do potęgi 3> = -5 * 8 = 40

-(-48a<do potęgi 2> + 10a)-(-4a-a<do potęgi 2> ) = 48a<do potęgi 2> - 10a + 4a + a<do potęgi 2> = 49a<do potęgi 2> - 6a = 49 * (-1/7)<do potęgi 2> - 6 * (-1/7) = 49 * 1/49 - 6/7 = 49/49 - 6/7 = 49/49 - 42/49 = 7/49 = 1/7
1 5 1
2010-03-18T20:13:57+01:00
A)
-3xy<do potęgi 3>-(2xy<do potęgi 3>=
-3xy³-2xy³=
-5xy³=
-5*1*2³=
-40

b)
-(-48a<do potęgi 2> + 10a)-(-4a-a<do potęgi 2> )=
-(-48a²+10a-(-4a-a²)=
48a²-10a+4a+a²=
49a²-6a=
49*(-1/7)²-6*(-1/7)=
49*1/49+6/7=
1+6/7=
1⁶/₇

2010-03-18T20:17:39+01:00
-3xy<do potęgi 3>-(2xy<do potęgi 3>) = -5xy<do potęgi 3> = -5 * 1 * 2<do potęgi 3> = -5 * 8 = 40

-(-48a<do potęgi 2> + 10a)-(-4a-a<do potęgi 2> ) = 48a<do potęgi 2> - 10a + 4a + a<do potęgi 2> = 49a<do potęgi 2> - 6a = 49 * (-1/7)<do potęgi 2> - 6 * (-1/7) = 49 * 1/49 - 6/7 = 49/49 - 6/7 = 49/49 - 42/49 = 7/49 = 1/7